2020
DOI: 10.1103/physrevresearch.2.033387
|View full text |Cite
|
Sign up to set email alerts
|

Kondo-assisted switching between three conduction states in capacitively coupled quantum dots

Abstract: We propose a nanoscale device consisting of a double quantum dot with strong intra-and interdot Coulomb repulsions. In this design, the current can only flow through the lower dot, but is triggered by the gate-controlled occupancy of the upper dot. At low temperatures, our calculations predict the double dot to pass through a narrow Kondo regime, resulting in highly sensitive switching characteristics between three well-defined statesinsulating, normal conduction, and resonant conduction.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Also, considering of systems consisting of two or more QDs in close proximity to each other have shown that in addition to the intra-dot Coulomb repulsion, the inter-dot Coulomb interaction plays an important role on transport properties of QDs [32][33][34]. For example, in the [35], the electronic transport properties of a double QD structure which are coupled via a strong inter-dot Coulomb interaction, has investigated and it is shown that the inter-dot Coulomb interaction can strongly affect the current through the QD. Also, the effect of Coulomb interaction on the thermoelectric properties of QDs has been the subject of many work [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Also, considering of systems consisting of two or more QDs in close proximity to each other have shown that in addition to the intra-dot Coulomb repulsion, the inter-dot Coulomb interaction plays an important role on transport properties of QDs [32][33][34]. For example, in the [35], the electronic transport properties of a double QD structure which are coupled via a strong inter-dot Coulomb interaction, has investigated and it is shown that the inter-dot Coulomb interaction can strongly affect the current through the QD. Also, the effect of Coulomb interaction on the thermoelectric properties of QDs has been the subject of many work [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%